RP-HPLC Method Development and Validation for the Simultaneous Estimation of Rosuvastatin and Ezetimibe in Tablet Dosage Form - Vadthya Rajashekar; K.Rajeswar Dutt; N.Ramathilagam (International Journal of Pharmacy and Analytical Research, 2014)
A simple reversed-phase high-performance liquid chromatographic (RP-HPLC) method has been developed and validated for simultaneous determination of Rosuvastatin and Ezetimibe in pharmaceutical tablet dosage form. Chromatographic analysis was performed on a Symmetry X-terra C8 (4.6mm x 100mm, 5m)column at ambient temperature with a mixture of ortho phosphoric acid buffer and Acetonitrile in the ratio 40:60 v/v as mobile phase, at a flow rate of 1.0 mL min-1 . UV detection was performed at 237 nm.. The retention times of Rosuvastatin and Ezetimibe were 2.490 and 3.173 min, respectively. The correlation coefficient of Rosuvastatin and Ezetimibe was found to be 0.999. Calibration plots were linear over the concentration ranges 10–50 μg mL-1 for Rosuvastatin and Ezetimibe, respectively. The Limit of detection was 1.626 and 0.918µg mL-1 and the quantification limit was 4.927 µg mL-1 and 2.783µg mL-1 for Rosuvastatin and Ezetimibe, respectively. The accuracy of the proposed method was determined by recovery studies and found to be 99.59% to 100.70%.The method was validated for accuracy,linearity,sensitivity,precision,robustness,system suitability Commercial tablet formulation was successfully analyzed using the developed method and the proposed method is applicable to routine analysis of determination of Rosuvastatin and Ezetimibe in pharmaceutical tablet dosage form.